THE INFLUENCE OF PERCEPTIONS OF TAX SYSTEM EFFECTIVENESS, TRUST IN THE GOVERNMENT, AND PERCEPTIONS OF CORRUPTION ON TAX COMPLIANCE MEDIATED BY TAXPAYER AWARENESS (Study on MSMEs Taxpayers of Grobogan Regency) - Inayah, Nur; Utomo, Budi (Economic and Science Faculty of Islamic State University, 2023)
The research was conducted to determine the effectiveness of the taxation system, trust in the government, and the perception of corruption in taxpayer compliance with taxpayer awareness as an intervening variable. The data was collected by disseminating a direct questionnaire to the Grobogan Regency MSMEs Taxpayer. This research type is quantitative with the number of respondent a total of 100 Grobogan Regency MSMEs recorded at Primary Tax Office Service in Blora. The data obtained is processed using the assistance of IBM SPSS version 25. The result of this study is that taxpayer compliance can be positively and significantly influenced by the perception of the effectiveness of the tax system and taxpayer awareness of taxpayer compliance. Still, trust in the government and corruption perception cannot influence taxpayer compliance. Taxpayer awareness can be influenced positively and significantly by the perception of the effectiveness of the tax system and trust in the government. Still, the awareness of taxpayers cannot be influenced by the perception of corruption. Taxpayer awareness can mediate the effect of the perception of the effectiveness of the taxation system and trust in the government on taxpayer compliance. In contrast, the awareness of taxpayers is unable to mediate the effect of corruption perception of taxpayer compliance.